The Effect of Interaction between Nanofillers and Epoxy on Mechanical and Thermal Properties of Nanocomposites: Theoretical Prediction and Experimental Analysis - S. Khostavan; M. Fazli; M. Ghorbanzadeh Ahangari; Y. Rostamiyan (Advances in Polymer Technology)
Interfacial interaction between host matrix and nanofillers is a determinative parameter on the mechanical and thermal properties of nanocomposites. In this paper, we first investigated interaction between carbon nanotube (CNT) and montmorillonite clay (MMT) absorbing on epoxy surface in a theoretical study based on the density functional theory (DFT) calculations. Results showed the interaction energy of -1.93 and -0.11 eV for MMT/epoxy and CNT/epoxy, respectively. Therefore, the interaction between epoxy polymer and MMT is of the chemisorptions type, while epoxy physically interacts with CNT. In addition, thermal and mechanical analyses were conducted on nanocomposites. In DSC analysis the glass transition temperature which was 70°C in neat epoxy composite showed an improvement to about 90°C in MMT nanocomposites while it was about 70°C for CNT nanocomposites. Finally, mechanical properties were investigated and MMT nanocomposite showed a change in compressive strength which increased from 52.60 Mpa to 72.07 and 92.98 Mpa in CNT and MMT nanocomposites, respectively. Also tensile strength improved to the value of 1250.69 Mpa MMT nanocomposites while it was about 890 Mpa in both CNT nanocomposite and neat epoxy composite which corresponds to the calculation result prediction.